Muscle strength reduction is related to muscle loss in women over the age of 40. - Fábio Lera Orsatti; Reinaldo Cesar Dalanesi; Nailza Maestá; Eliana Petri Aguiar Nahas; Roberto Carlos Burini (Universidade Federal de Santa Catarina, 2011)
The objective of this study was to compare the influence of age on muscle mass (MM) and muscle strength (MS) of the upper and lower limbs in women older than 40 years. Fifty-two volunteers were divided into three age groups: 40-49 years (G40, n = 16), 50-59 years (G50, n = 18), and 60-70 years (G60, n = 18). MM was evaluated by bioelectrical impedance and MS by the 1RM test. One-way analysis of variance, Duncan's test and Pearson's correlation coefficient were used for statistical analysis. There was a significant difference in MM (p < 0.05) of 10.1% between G40 and G50 and of 7.5% between G50 and G60, corresponding to 16.8% in the two decades (G40/G60). Lower limb MS was 16.4% lower between G40 and G50 and 12.5% between G50 and G60, corresponding to 25.3% in the two decades (p < 0.05). In the upper limbs, there was no significant difference in MS between G40 and G50 (3.3% and 2.5% bench curl) or between G50 and G60 (17.5% and 9.6%), corresponding to 20.2% and 12.2% in the two decades, respectively. The sum of MS was corrected by MM (MS/MM) and no significant differences were observed between groups. Comparison of MM and MS showed a closer correlation in the lower limbs (r = 0.57) when compared to the upper limbs (r = 0.42 and r = 0.41, respectively). In conclusion, women presented lower MM and MS in the lower limbs as early as in the fifth decade of life. MS/MM does not change in women between 40 and 60 years when compared according to age group. Reduced MM seems to be an important for the lower MS observed in women between 40 and 60 years of age.